Gandhian Thought : a study of tradition and modernity - Maharajan, M. (New Delhi : Sterling Publishers, 1996)
On the fundamental ideas of Gandhi's socio-political philosophy.
Includes bibliographical references (p. 142]-148) and indexes.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Political and social views